Myeloid‐derived suppressor cell functionality and interaction with Leishmania major parasites differ in C57BL/6 and BALB/c mice. Issue 11 (19th September 2014) - Schmid, Maximilian; Zimara, Nicole; Wege, Anja Kathrin; Ritter, Uwe
<x xml:space="preserve">Abstract</x> Myeloid‐derived suppressor cells (MDSCs) represent a heterogeneous population of CD11b+ cells. According to the surface molecules Ly6G and Ly6C (where Ly6G and Ly6C are lymphocyte antigen 6, locus G and C, respectively), MDSCs are further divided into monocytic (Mo‐MDSCs, CD11b+/Ly6Chigh/Ly6G−) and polymorphonucleated suppressor cells (PMN‐MDSCs, CD11b+/Ly6Cint/Ly6G+). Most published manuscripts focus on the suppressive role of MDSCs in cancer, whereas their impact on adaptive immunity against obligatory intracellular parasites is not well understood. Furthermore, it is not clear how the genetic background of mice influences MDSC functionality. Therefore, we implemented an experimental model of leishmaniasis, and analyzed MDSC maturation and the impact of MDSCs on the parasite‐specific T‐cell responses in resistant C57BL/6 and susceptible BALB/c mice. This experimental setup demonstrated the impaired ability of BALB/c mice to produce Mo‐MDSCs when compared with C57BL/6 mice. This phenotype is detectable after subcutaneous infection with parasites and is specifically represented by a reduced accumulation of Mo‐MDSCs at the site of infection in BALB/c mice. Moreover, infected C57BL/6‐derived MDSCs were able to suppress Leishmania‐specific CD4+ T‐cell proliferation, whereas BALB/c‐derived MDSCs harboring parasites lost this suppressive function. In conclusion, we demonstrate that (i) genetic background defines MDSC differentiation; and (ii) Leishmania major parasites are able to modulate the suppressive effect of MDSCs in a strain‐dependent manner.